1983
DOI: 10.1038/bjc.1983.177
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of socioeconomic factors and clinical findings in Hodgkin's disease, and reanalysis of previous data regarding chemical exposure

Abstract: Summary An association between malignant lymphoma (both Hodgkin's disease (HD) and non-Hodgkin lymphoma) and exposure to organic solvents, phenoxy acids, or chlorophenols was previously reported. A reanalysis of this investigation regarding the cases with HD and exposure to various chemicals was performed and resulted in comparable findings to the whole group of malignant lymphoma. There was an overrepresentation of cases with primary involvement of the gastrointestinal tract which was associated with exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 23 publications
1
26
1
Order By: Relevance
“…The increasing trend in non-Hodgkin's lymphoma may be due to the widespread introduction of herbicides since the 1950s and a twenty to thirty year average latent period. There was no association between herbicides and the development of Hodgkin's disease in the Kansas study (Hoar et al, 1986), which appears consistent with the Yorkshire and Minnesota data, but contrasts with findings from Sweden (Hardell et al, 1981;Hardell & Bengtsson, 1983).…”
contrasting
confidence: 47%
See 1 more Smart Citation
“…The increasing trend in non-Hodgkin's lymphoma may be due to the widespread introduction of herbicides since the 1950s and a twenty to thirty year average latent period. There was no association between herbicides and the development of Hodgkin's disease in the Kansas study (Hoar et al, 1986), which appears consistent with the Yorkshire and Minnesota data, but contrasts with findings from Sweden (Hardell et al, 1981;Hardell & Bengtsson, 1983).…”
contrasting
confidence: 47%
“…lymphoma in persons frequently exposed to herbicides (Hardell et al, 1981;Hardell & Bengtsson, 1983;Hoar et al, 1986). The increasing trend in non-Hodgkin's lymphoma may be due to the widespread introduction of herbicides since the 1950s and a twenty to thirty year average latent period.…”
mentioning
confidence: 99%
“…Subsequent studies on malignant lymphoma including both Hodgkin's disease and NHL showed increased odds ratios for exposure to phenoxyacetic acids, chlorophenols, or organic solvents including benzene (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…In particular, the Ranch Hand study did not show an increase in these tumors, 62 nor did a study of 33,833 Army and Marine Vietnam veterans, 19 the Selected Cancers Study, 16 a case-control study of 283 Vietnam-era veterans with Hodgkin disease, 68 or studies of veterans in Michigan, 29 New York, 26 or other states. However, Hodgkin disease was linked to phenoxy herbicide and chlorophenol exposure in one case-control study in Sweden, 64,69 and another yielded similar results, although without statistical significance. 65 Many studies of farmers and agricultural workers show an increase in Hodgkin disease, which may relate to herbicide exposure.…”
Section: Hodgkin Diseasementioning
confidence: 50%